PERFEKSIONISME: PENYEBAB MENTAL GEN Z MENJADI PEOPLE PLEASURE - Aulia Marthasya; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
This article examines the phenomenon of “People Pleasure” among Generation Z, which is the tendency to please others rooted in perfectionism. Through the framework of symbolic interaction theory, this research focuses on how individuals shape meaning from social interaction and communication, as well as the importance of setting self-limits to deal with such behavior. Findings suggest that perfectionism can be a trigger for mental dissatisfaction, as individuals feel pressured to meet their own and others' expectations. This tendency contributes to various mental health problems, such as anxiety and depression. Therefore, applying the concept of “Self Boundaries” is crucial to maintain a balance between meeting the needs of others and maintaining mental health. This study proposes several strategies, such as increasing self-awareness, setting clear boundaries, and communicating effectively to help individuals overcome the behavior of “People Pleasure.” Overall, this study provides useful insights into the impact of perfectionism and social media on “People Pleasure” behavior, and offers practical approaches to improve Generation Z's mental health in the face of complex social pressures. It is hoped that the results of this study can serve as a reference for the development of interventions in the context of psychology and sociology.